DESCRIPTION OF PARENTS' KNOWLEDGE LEVEL ABOUT WORMS IN PRE-SCHOOL CHILDREN TUNAS MULIA KINDERGARTEN - Rahmadhani, Audhyra; Sulystiono, Dony (Global Ten Public Health and Nursing Journal, 2023)
Worm infestation is still a serious problem in Indonesia. Worm infestation is often considered a trivial disease by most people. In this case this disease can reduce the level of health of children e.g. anemia, growth and development disorders, cognitive development disorders, lazy activities and weight gain, The research design used in this research is "descriptive" research, which is a research design that aims to describe present events, carried out systematically and emphasizes factual data rather than inference by conducting surveys on variables. Based on the results of the discussion that has been presented, the researcher can conclude several things based on the objectives achieved in the research conducted at Tunas Mulia Kindergarten, namely that the level of parental knowledge about the prevention of worms in the good category is 41 people (91.1%).The incidence of helminthiasis based on the Sidoarjo District Health Office profile is 7.22 percent or around 174 children out of 2,400 children who were weighed. They were found in 19 villages.It is expected that parents generally have the motivation to increase their knowledge and seek information about the impacts that arise if not treated immediately through counseling and from various media.